THE DEVELOPMENT AND THE EFFECTIVENESS OF ENGLISH E-LEARNING - Agustina, Noni; Budhisantosa, Nugroho (Universitas Pendidikan Ganesha, 2018)
In the twenty first century, teachers are required to have a digital literacy skill. They must be able to integrate technology in learning process. It was already conducted by a teacher in one of public junior high schools in Jakarta. She searched the materials from the internet but she had a problem to adjust the learning materials to her studentsâ€™ needs and characteristics. Therefore, this study was undertaken to explore deeply how to develop e-learning in English class based on her studentsâ€™ needs and characteristics and examined its effectiveness. This study employed research and development methodology with qualitative and quantitative approach. The participants were an English teacher and the first graders of junior high school. The result showed that this e-learning consisted of listening, reading, and grammar used PHP, Framework Bookstrap, MySQL, Adobe Flash and Adobe Illustrator to make some animated videos. The result also showed that the learning English using e-learning was more effective than without it. The difference of mean was 5.53 %. It was also different significantly between them (Sig.2-tailed 0.011 < 0.05). It is expected to contribute as supplemental learning media in English learning process.Â Key words: E-learning development, e-learning, and English learning